2012
DOI: 10.1111/j.1744-7909.2012.01144.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differentially Senescing Mutants of Wheat and Impacts on Yield, Biomass and Nitrogen PartitioningF

Abstract: Increasing photosynthetic capacity by extending canopy longevity during grain filling using slow senescing stay-green genotypes is a possible means to improve yield in wheat. Ethyl methanesulfonate (EMS) mutated wheat lines (Triticum aestivum L. cv. Paragon) were screened for fast and slow canopy senescence to investigate the impact on yield and nitrogen partitioning. Stay-green and fast-senescing lines with similar anthesis dates were characterised in detail. Delayed senescence was only apparent at higher nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 32 publications
6
51
1
1
Order By: Relevance
“…The current study reveals a significant positive relationship between the onset of leaf senescence and grain number per m 2 in each year regardless of the assessment methods for senescence dynamics (data not shown). It suggests that more grains defined before anthesis require a longer phase of functional photosynthesis, and a similar result has been reported in a staygreen mutant (Derkx et al, 2012). Thus, it seems that delayed leaf senescence is a favorable trait for both grain size and grain number, giving rise to high yield potential.…”
Section: Early Anthesis and Delayed But Fast Leaf Senescence As An Isupporting
confidence: 62%
“…The current study reveals a significant positive relationship between the onset of leaf senescence and grain number per m 2 in each year regardless of the assessment methods for senescence dynamics (data not shown). It suggests that more grains defined before anthesis require a longer phase of functional photosynthesis, and a similar result has been reported in a staygreen mutant (Derkx et al, 2012). Thus, it seems that delayed leaf senescence is a favorable trait for both grain size and grain number, giving rise to high yield potential.…”
Section: Early Anthesis and Delayed But Fast Leaf Senescence As An Isupporting
confidence: 62%
“…A functional stay-green trait enables the plant to synthesize and store greater levels of assimilates, which can lead to increased crop yields under certain environments (Richards 2000;Christopher et al 2008;Zhou et al 2011;Derkx et al 2012). Our photosynthesis measurements showed that the GPC-1 mutants maintain photosynthetic activity for longer than the control lines; hence we can classify the GPC-1 mutants as functional stay-green mutants.…”
Section: Stay-green Phenotype and Its Potential Effects On Yield Compmentioning
confidence: 83%
“…However, Derkx et al . (2010, 2012) found that both fast‐senescing and stay‐green mutants of wheat had higher grain N concentrations than the wild type. This conflicting evidence suggests the involvement of different physiological mechanisms through which increased grain N concentrations may be achieved.…”
Section: Discussionmentioning
confidence: 99%